2014
DOI: 10.1371/journal.pone.0106404
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI Findings Predict Two-Year Postoperative Clinical Outcome in Lumbar Spinal Stenosis

Abstract: PurposeTo study the predictive value of preoperative magnetic resonance imaging (MRI) findings for the two-year postoperative clinical outcome in lumbar spinal stenosis (LSS).Methods84 patients (mean age 63±11 years, male 43%) with symptoms severe enough to indicate LSS surgery were included in this prospective observational single-center study. Preoperative MRI of the lumbar spine was performed with a 1.5-T unit. The imaging protocol conformed to the requirements of the American College of Radiology for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Preoperative MRI may be helpful for selecting the optimal operation methods and predict the prognosis of LBP patients after surgical treatment. Kuittinen et al reported that preoperative MRI of the lumbar spine could predict the outcome of LBP patients after surgical treatment in a 2-year follow up period (27). In their study, the additional MRI indicated that the severe lumbar spinal central stenosis could predict lower LBP and leg pain when compared to that in patients with moderate central stenosis after surgical treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Preoperative MRI may be helpful for selecting the optimal operation methods and predict the prognosis of LBP patients after surgical treatment. Kuittinen et al reported that preoperative MRI of the lumbar spine could predict the outcome of LBP patients after surgical treatment in a 2-year follow up period (27). In their study, the additional MRI indicated that the severe lumbar spinal central stenosis could predict lower LBP and leg pain when compared to that in patients with moderate central stenosis after surgical treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, the addition of arthrodesis to decompression was not separately evaluated. Kuittinen et al [ 13 ] found that severe central stenosis and one-level central stenosis predict a positive outcome of LSS surgery, while multilevel stenosis is associated with a negative outcome. Herno et al [ 14 ] found that patients with previous back surgery had a significant negative impact on the outcome of reoperation for LSS.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar spinal stenosis (LSS) has grown in importance over the past decade in response to the rising older population [1][2][3] and has become the most common surgical indication for people over 65 years of age. 1,4 In the United States, Deyo et al 5 found that from 2002-2007, there were 135.5-137.5 persons 100 000 Medicare beneficiaries aged 65 and older who underwent lumbar stenosis surgery. In 2007 alone, hospital costs for LSS operations accounted for almost $1.65 billion (2009 dollars).…”
Section: Introductionmentioning
confidence: 99%